ROLE OF MAHILA SAMAKHYA KARNATAKA IN THE EMPOWERMENT OF RURAL WOMEN THROUGH EDUCATION PROGRAMMES AT MYSURU DISTRICT - P, Prathibha; B., Gururaj, (International Journal of Psychosocial Rehabilitation, 2020)
Mahila Samakhya programme was initiated in 1989 by the Ministry of Human Resource Development (MHRD) under the Department of Education, Government of India with the aim of empowering rural women. The article assesses the various Educational programmes undertaken by MSKn at Mysuru District. The sample size comprises of 360 women respondents and the data collected was analyzed using descriptive and inferential statistics. The results reveal that, 90% of the respondents found the programme to be extremely effective, more than 85% possess awareness on education mainly due to this programme and over 75% of the knowledge gained is utilized by the respondents to become confident and also to encourage their children and family to obtain education. It is concluded that, MSkn programme has played a significant role in the empowerment of rural women through Education programmes.